Respuesta :
Answer:
-5 and 3
Step-by-step explanation:
Simply set x+5 equal to zero.
- x+5=0
- x=-5
Set x-3 equal to zero.
- x-3=0
- x=3
The solution to the given equation, (x + 5)(x -3) = 0, is calculated as: x = -5; x = 3.
How to Find Solutions of an Equation?
To find the solutions of an equation, isolate the values of x in each of the factors of the equation.
Given the equation, (x + 5)(x -3) = 0, we have:
x + 5 = 0; x = -5
x - 3 = 0; x = 3
The solution is, x = -5; x = 3
Learn more about solution of an equation on:
https://brainly.com/question/13729904